Model Proses Pengambilan Keputusan Kepala Sekolah dalam Meningkatkan Mutu Lulusan Berdaya Saing di Sekolah Menengah Kejuruan - Bakti Toni Endaryono; Tjipto Djuhartono (SAP (Susunan Artikel Pendidikan), 2023)
A decision-making process of vocational high schools in improving the quality of competitive graduates with the aim of solving problems that occur at school so that it is necessary to have the accurate model so that decisions can be accepted and can run well, the purpose of this study is specifically to discuss and gain new knowledge and discoveries to create a chart model of the decision-making process in improving the quality of the competitive graduates in Vocational High Schools, The method in this study is descriptive methods with a Qualitative approach to provide a systematic, factual and accurate description of the facts of the object of research, The research was conducted in four (4) months at Bistek Vocational High School (Business and Technology) Bekasi, the research activities were carried out in three stages including the preparation stage, the research implementation stage and the final stage of preparing the research report, The results of this study were the decision-making process carried out by SWOT analysis, the decision-making process had five appropriate steps, the decision-making process with a rational model by considering aspects that had a positive or negative impact based on a system of ethical values by prioritizing honesty, responsibility, good faith, respect and humility, harmony and tolerance as well. Patience and sincerity to forgive each other, which was realized in the pattern of relationships or relationships between patience and forgiveness of conditions that can be done through patience and sincerity to forgive each other, all components of the school environment.